Rare cause of manic period trigger in bipolar mood disorder: testosterone replacement. (3rd August 2018) - Elboga, Gulcin; Sayiner, Zeynel Abidin
Abstract : Hypogonadotropic hypogonadism is a rare congenital disorder characterised by the deficiency and the absence of puberty and infertility. It is caused by the deficient production, secretion or action of gonadotropin-releasing hormone, which is the master hormone regulating the reproductive axis. Gonadotropin-releasing hormone or gonadotropin injections and testosterone replacement therapy are required in the treatment of this disorder. Psychiatric symptoms and disorders may be seen with the use of anabolic androgenic steroids. In this case report, we present a case report in which a patient had behavioural symptoms in childhood and develops bipolar disorder after testosterone replacement therapy. This patient was reached to the remission by increasing the doses of psychiatric drugs without interfering with hormonal therapy. It should be considered that patients receiving testosterone replacement therapy may develop bipolar disorder or trigger mood changes in bipolar mood disease, so behavioural and mood state changes should be closely followed in patients who have bipolar mood disease.